Administrators in Action—Managing Public Monies and Processing Emotion in School Activities: A Teaching Case Study. (September 2015) - Tenuto, Penny L.; Gardiner, Mary E.; Yamamoto, Julie K.
This teaching case describes school administrators in action performing day-to-day leadership tasks, managing public funds in school activities, and interacting with others appropriately. The case focuses on administrative challenges in handling and managing school activity funds. A method for processing emotion is discussed to assist administrators in building capacity in themselves and others. Self-reflection helps leaders to understand themselves and others, improve communication, and avoid misunderstandings, strengthening capacity to lead. Teaching notes, questions for reflection, and an application activity are also included. The case was developed for use within educational leadership pre-service and for professional learning by practicing school administrators.